Inotuzumab ozogamicin as chemotherapy-sparing salvage in a 67-year-old man with primary refractory B-cell acute lymphoblastic leukemia with high-risk genomic features. (2019) - Yang, Xiaochuan; Sen, Filiz; Geyer, Mark B.
Abstract: Older adults with acute lymphoblastic leukemia (ALL) continue to have a poor prognosis, in part due to greater chemotherapy-related toxicities. We herein report a 67-year-old man with Philadelphia chromosome (Ph)-negative B-cell ALL, who exhibited refractoriness to 3 different regimens of induction chemotherapy and experienced multiple complications including intracranial bleeding and respiratory failure, who achieved minimal residual disease (MRD)-negative complete response (CR) after a single cycle of inotuzumab ozogamicin (IO). His ALL was characterized by several high-risk mutations, which may have contributed to chemotherapy-refractory disease. Our case supports incorporating IO into front-line induction regimens for older adults with high-risk B-cell ALL.